1974
DOI: 10.1029/wr010i002p00246
|View full text |Cite
|
Sign up to set email alerts
|

Application of seasonal parametric linear stochastic models to monthly flow data

Abstract: Stochastic linear models are fitted to hydrologic data for two main reasons: to enable forecasts of the data one or more time periods ahead and to enable the generation of sequences of synthetic data. These techniques are of considerable importance to the design and operation of water resource systems. Short sequences of data lead to uncertainties in the estimation of model parameters and to doubts about the appropriateness of particular time series models. A premium is placed on models that are economical in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 8 publications
0
45
0
2
Order By: Relevance
“…An inherent advantage of the SARIMA family of models is that few model parameters are required for describing time series, which exhibit non-stationarity both within and across the seasons. Some useful applications of these models in seasonal river flow forecasting are reported in McKerchar and Dellur (1974), Panu et al (1978), Cline (1981), Govindaswamy (1991) and Yurekli et al (2005). Hydrologists have also widely used stochastic analogy for the analyzing and modeling of hydrologic time series.…”
Section: Background Information On Application Of Stochastic Modelsmentioning
confidence: 98%
“…An inherent advantage of the SARIMA family of models is that few model parameters are required for describing time series, which exhibit non-stationarity both within and across the seasons. Some useful applications of these models in seasonal river flow forecasting are reported in McKerchar and Dellur (1974), Panu et al (1978), Cline (1981), Govindaswamy (1991) and Yurekli et al (2005). Hydrologists have also widely used stochastic analogy for the analyzing and modeling of hydrologic time series.…”
Section: Background Information On Application Of Stochastic Modelsmentioning
confidence: 98%
“…An inherent advantage of the SARIMA family of models is that few model parameters are required for describing time series, which exhibit nonstationarity both within and across seasons. Some useful applications of these models in seasonal river flow forecasting are reported in McKerchar and Delleur (1974); Panu et al (1978); Cline (1981); Govindasamy (1991); Sidhu (1995 Kavvas and Delleur (1975) have shown, both from analytical and empirical results, that seasonal and/or nonseasonal differencing, although very effective in the removal of hydrologic periodicities, distorts the original spectrum, thus making it impractical or impossible to fit an ARMA model for hydrologic simulation or synthetic generation. McKerchar and Delleur (1974); Delleur et al (1976) have shown that the forecasting capabilities of seasonally differenced models may be impaired by the fact that they may not take into account the seasonal variation in the seasonal standard deviations.…”
Section: Introductionmentioning
confidence: 97%
“…Auto-regressive (AR) and auto-regressive integrated moving average (ARIMA) models were applied to forecast monthly flows in Wabash River, Indiana, USA [20]. Noakes et al [13] assessed the forecasting ability of ARMIA, auto-regressive moving average (ARMA) and AR models in forecasting monthly flows in 30 rivers in North and South America.…”
Section: Time Series Modelmentioning
confidence: 99%